Clinical and microbiological properties of Staphylococcus lugdunensis skin infections. Issue 8 (13th June 2018) - Zaaroura, Hiba; Geffen, Yuval; Bergman, Reuven; Avitan‐Hersh, Emily
Abstract: Staphylococcus lugdunensis is an emerging pathogen in skin and soft tissue infections that was previously considered a commensal. The aim of this study was to elucidate the characteristics of skin infections by S. lugdunensis and its appropriate management, in a tertiary referral medical center. The clinical files, bacterial cultures and histopathology reports of all S. lugdunensis isolates from skin infections over a period of 8 years (September 2009–September 2017) were reviewed. S. lugdunensis was isolated from 29 patients with skin infections, aged 7–89 years (mean 33.3 years). A state of immune suppression (drug‐induced, malignancy or diabetes) was present in five patients (17%). Folliculitis and cutaneous pustulosis were the most common presentations (16 cases, 55%), followed by secondary infection of hidradenitis suppurativa (five cases, 17%). Other sources of isolation were infected molluscum contagiosum (two cases), folliculitis decalvans (one case), dissecting cellulitis (one case), abscess (one case), cyst (one case), impetigo (one case) and granuloma after trauma (one case). The in vitro antibiotic sensitivity tests showed susceptibility to most tested antibiotics, although a few isolates were resistant to gentamycin, penicillin and oxacillin. In 19 of 20 patients for whom follow ups were available, cutaneous manifestations improved or resolved with proper local and/or oral antibiotic therapy. S. lugdunensis may play a role as a primary or secondary pathogen in various skin infections, most commonly folliculitis and pustulosis. Proper antibiotic therapy may lead to improvement or resolution.